KEPEMIMPINAN KOLEKTIF BERBASIS CONTINUAL IMPROVEMENT DI SMAIT ABU BAKAR BOARDING SCHOOL KULON PROGO - Akhsanul Fuadi (IAIN Ponorogo, 2020)
AbstractThis research explores management patterns as the strategy of the SMAIT Abu Bakar Boarding School Kulon Progo School (SMAIT ABBS KP) in realizing to become superior schools, SMAIT ABBS KP has challenges in making it happen. This School applies the principle of collective leadership with a continuous improvement strategy to realize new schools that have excellence predicate in accreditation and are leading in the achievements, where management is based on local excellence namely the power of human resources to create new schools that excel in accreditation.This research is a qualitative study that describes in detail and in depth all conditions in a context, about something that happens in the field. The results showed that the SMAIT ABBS KP implements collective leadership with a continual improvement strategy to create a superior school, so that even though it was only established in 2017, a lot of achievements were achievedby SMAIT ABBS KP. Some of them are: (1) schools with a predicate with an accred itation score of 94 (A) (2) getting various kinds of championships, both in academic, religious and other non-academic fields, (3) the realization of a compact and harmonious work team as provision to achieve progressive achievements AbstrakPenelitian ini menggali pola managemen sebagai strategi SMAIT Abu Bakar Boarding School Kulon Progo (SMAIT ABBS KP) dalam mewujudkan sekolah yang unggul, karena sebagai sekolah baru, SMAIT BBS KP mempunyai tantangan dalam mewujudkannya. SMAIT ABBS KP menerapkan prinsip kepemimpinan kolektif dengan strategi continual improvement untuk mewujudkan sekolah baru yang berpredikat unggul dalam akreditasi dan terdepan dalam prestasi, di mana manajemen tersebut dilandaskan pada keunggulan lokal yaitu kekuatan SDM untuk mewujudkan sekolah baru yang unggul dalam akreditasi dan terdepan dalam prestasi. Penelitian ini adalah penelitian kualitatif yang mendeskripsikan secara rinci dan mendalam segala potret kondisi dalam suatu konteks, tentang sesuatu yang terjadi di lapangan.Hasil Penelitian menunjukkan bahwa SMAIT ABBS KP menerapkan kepemimpinan kolektif dengan strategi continual improvement untuk mewujudkan sekolah yang unggul, sehingga walaupun baru berdiri tahun 2017 banyak prestasi yang sangat mengembirakan dan membanggakan di raih oleh SMAIT ABBS KP, karena sebagai sekolah yang baru 3 (tiga) tahun, telah berhasil meraih prestasi. Beberapa di antaranya adalah: (1) sekolah berpredikat unggul dalam akreditasi dengan meraih nilai 94 (A) (2) memperoleh berbagai macam kejuaraan, baik dalam bidang akademik, keagamaan dan non akademik lainnya, (3) terwujudnya tim kerja yang kompak dan harmonis sebagai bekal untuk melejitkan prestasi yang progressive.